A Case of Unicornuate Uterus with a Non-Communicating Non-Cavitated Rudimentary Horn Diagnosed During Laparoscopy for Contralateral Adnexal Torsion - Canda, Tunç; Demir, Namık; Doğanay, Latife (Gynecology Obstetrics & Reproductive Medicine, 2008)
Mullerian duct abnormalities are not very rare among women and can cause problems of fertility, pregnancy or pelvic pain. Diagnosis of these abnormalities is usually incidental. We report a rare case with no functional cavity non-communicating rudimentary horn diagnosed while performing laparoscopy for contralateral adnexial torsion due to corpus hemorrhagicum cyst.